Physical activity and sedentary screen time in obese and overweight children living in different environments - Raistenskis, Juozas; Sidlauskiene, Aurelija; Cerkauskiene, Rimante; Burokiene, Sigita; Strukcinskiene, Birute; Buckus, Raimondas (Central European Journal of Public Health, 2015)
AIM: To assess the relationship of children's physical activity and sedentary screen time with overweight and obesity in children living in different environments (town and city) in Lithuania. METHODS: An analysis of anthropometric data from 532 children living in town and city areas was performed. A youth physical activity questionnaire (YPAQ) was conducted to evaluate physical activity and sedentary screen time. RESULTS: The prevalence of overweight and obesity among the children was 25.5% in the town and 18.6% in the city. Children living in the town on average engaged 9.3 min/day less in moderate to vigorous physical activity (p=0.050) and had 33.2 MET-min/day lower energy expenditure than children living in the city. Sedentary screen time was extremely high on weekends in both town and city children. CONCLUSIONS: A higher prevalence of overweight and obesity and a lower amount of moderate-to-vigorous physical activity was found in children living in the town compared to children living in the city.
Keywords: obezita dětí a dospívajících; Sedentary Behavior; průzkumy a dotazníky; Female; Overweight; Anthropometry; Prevalence; dítě; Television; Urban Population; ženské pohlaví; sedavý životní styl; průřezové studie; Surveys and Questionnaires; Adolescent; pohybová aktivita; energetický metabolismus; lidé; Suburban Population; Litva; Energy Metabolism; antropometrie; Computers; prevalence; Cross-Sectional Studies; Lithuania; Male; televize; městské obyvatelstvo; nadváha; Motor Activity; Child; předměstské obyvatelstvo; počítače; mužské pohlaví; mladiství; Pediatric Obesity; Humans